Management of Acinetobacter baumannii infection of burn wound with the evidence of sepsis - K Mathangi Ramakrishnan; Bala Ramachandran; K G Ravikumar; K Ravikumar; Sulochana Putli; V Jayaraman; Mathivanan; Ravi; Arumugam Ganamani; Mary Babu (Wolters Kluwer Medknow Publications, 2019)
Introduction: Acinetobacter baumannii infection of a burn wound is a serious infection causing significant morbidity and mortality. Clinical Presentation: Acinetobacter can cause wound colonization, infection, invasive sepsis, and with or without septic shock. We present a series of five cases and management. Prompt medical and surgical treatments are essential to improve the outcome. Conclusion: Awareness of the presence of infection and detection of local sensitivity pattern of the organism will lead to initiation of the correct antibiotic.